SPENDING WELL: HOW TIME PERSPECTIVES IMPACT CONSUMER VALUES AND FINANCIAL DECISIONS AMONG MIDDLE-AGED ADULTS. Issue 2 (3rd April 2019) - Leonard, Sam; Zhang, Jia Wei; Howell, Ryan
Abstract : The current research extends the time perspective literature by exploring the relationships between time perspectives and financial outcomes across several adult age groups. In combining various demographically diverse samples, our study includes a total of 9, 065 adults that completed some form of the Zimbardo Time Perspective Inventory (ZTPI). We found that people who are Future-oriented tend to have more responsible financial lifestyles. On the other hand, Past-Negative, Present-Hedonism, and Past-Fatalism orientations are associated with more detrimental financial lifestyles. Thus, the greater the deviation from a balanced time perspective middle-aged adults were, the (1) more they reported being materialistic, (2) more impulsive, compulsive, and conspicuous they were when shopping, and (3) less financially secure they felt. Also, our mediation models revealed that increased impulsive buying, compulsive buying, and conspicuous consumption partially mediated the negative relation between Past-Negative and financial security. However, decreased conspicuous consumption partially mediated the positive relation between Future and financial risk tolerance. We discuss potential ways to shape individual time perspectives, the developmental implications for time perspectives, consumer profiles, and well-being, as well as limitations.